Atmospheric circulation in northern hemisphere and north atlantic oscillation - Александр Вадимович Холопцев; Мария Павловна Никифорова; Дарья Андреевна Астафьева (ScienceRise, 2015)
Conditions under which statistical connections of interannual changes of repitition duration periods in Northern hemisphere of elementary circulation mechanisms associated to meridional northern and meridional southern groups with variations of North Atlantic oscillation are significant were revealed. It is shown, that the characteristics changes of these connections taking place in modern period can be caused by distribution changes of distribution of sea surface temperatures